Pregled slovenske esejistike na temo slovenske literarne ustvarjalnosti - Bergles, Katja (Slavia Centralis, 2020)
Overview of a Slovenian essay on the Subject of Slovenian Literary ProductionLiterature (within the framework of which the authors treat contemporary literary occurrences, literary trends, periods and forms, their own or foreign works, ontological and phenomenological questions concerning literature and art in general) occupies a visible place in the Slovenian essay. This article discusses a minor thematic part of one of the more important problem circles that formed in the Slovenian essayist corpus between 1995 and 2010 and gives a short introduction to some essays dealing with Slovenian literary production.
Keywords: essay; Slovenian essay; Slovenian literature; literary essay